World Catalogue of the family Thaumaleidae (Diptera: Culicomorpha) - Sinclair, Bradley J.; Pivar, Robert J.; Arnaud, Paul H., Jr. (Zootaxa, 2022)
Family, genus and species group names in the family Thaumaleidae (Diptera: Culicomorpha) are catalogued, including information on name-bearing types, distribution by country and 428 references to all literature known to us pertaining to this family. The Thaumaleidae or madicolous midges are known from 202 species in the following seven genera: Afrothaumalea Stuckenberg, 1960 (3 species), Androprosopa Mik, 1898 (59 species), Austrothaumalea Tonnoir, 1927 (44 species), Neothaumalea Pivar, Moulton & Sinclair, 2018 (1 species), Niphta Theischinger, 1986 (14 species), Thaumalea Ruthe, 1831 (77 species) and Trichothaumalea Edwards, 1929 (4 species). In addition, one fossil genus and species are known (Mesothaumalea fossilis Kovalev). Published species distributions are provided, noting country and biogeographic region; specimen data representing new records for species are listed. The following new combinations, originally assigned to Thaumalea, are proposed: Androprosopa baminana (Yang, 2003) comb. nov., Androprosopa zhejiangana (Yang, 1998) comb. nov.